The Role of Cardiac Magnetic Resonance in Myocardial Infarction and Non-obstructive Coronary Arteries - Liang, Kate; Nakou, Eleni; Del Buono, Marco Giuseppe; Montone, Rocco Antonio; D'Amario, Domenico; Bucciarelli-Ducci, Chiara (Frontiers in Cardiovascular Medicine, 2022)
Myocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA) accounts for 5-15% of all presentations of acute myocardial infarction. The absence of obstructive coronary disease may present a diagnostic dilemma and identifying the underlying etiology ensures appropriate management improving clinical outcomes. Cardiac magnetic resonance (CMR) imaging is a valuable, non-invasive diagnostic tool that can aide clinicians to build a differential diagnosis in patients with MINOCA, as well as identifying non-ischemic etiologies of myocardial injury (acute myocarditis, Takotsubo Syndrome, and other conditions). The role of CMR in suspected MINOCA is increasingly recognized as emphasized in both European and American clinical guidelines. In this paper we review the indications for CMR, the clinical value in the differential diagnosis of patients with suspected MINOCA, as well as its current limitations and future perspectives.